Energia de briquetes produzidos com rejeitos de resíduos sólidos urbanos e madeira de Eucalyptus grandis - Gonçalves, José E. [UNESP]; Sartori, Maria M. P. [UNESP]; Leão, Alcides Lopes [UNESP] (FapUNIFESP (SciELO), 2009)
The incentive for consumption and production in large quantity in modern society generates enormous amounts of urban solid residues in the form of municipal solid waste (MSW). With the intention of reducing these residues of the municipal waste tips and to generate energy, briquettes with mixtures of MSW and residues of Eucalyptus grandis were produced. The briquettes were manufactured with 0, 5, 10, 15, 20 and 25% of MSW in the mixture with wood waste and 12% of moisture content. The analyzed parameters used to choose the best treatments were combustion analysis versus ash content, mechanical strength and energy content. The briquettes up to 10% of MSW showed low resistance, and above 15% showed large increase in ash content. Therefore, the treatment that fulfilled the requirements for combustion versus ash content and mechanical resistance was of at least 15% of MSW, since the source of the ash is unidentified. Considering the net energy content, the best treatment was 25% of MSW, with 17,175 kJ kg-1. Nevertheless, it is strongly advised that further studies related to gas emissions are necessary.
Energy from briquettes produced from remains of urban solid residues and wood of Eucalyptus grandis
Keywords: Biomass; Calorific power; Trash; Eucalyptus; Eucalyptus grandis